Dereplication of terpenes and phenolic compounds from Inga edulis extracts using HPLC-SPE-TT, RP-HPLC-PDA and NMR spectroscopy - Lima, Nerilson M. [UNESP]; Andrade, Teresinha J. A. S.; Silva, Dulce Helena S. [UNESP] (Taylor & Francis, 2020)
Inga edulis is traditionally used as anti-inflammatory and antidiarrheal and has been investigated as potential sources of biologically active natural products. In this study, dereplication strategy using HPLC-SPE-TT, RP-HPLC-PDA and NMR spectroscopy was employed, and this resulted in the identification of sixteen compounds from the leaves extract of I. edulis, including four triterpenes (lupeol, α-amirin, olean-18-ene acid and frideline), three flavonoids, eight phenolic acids, an anthocyanin derived from delphinidin-3-glycoside and a mixture of five acylated anthocyanins. The chemical identification was performed based on NMR data, chemosystematics aspects, UV spectra and by comparison with the retention time and UV spectra of authentic standards. The metabolic profile of the species indicated the presence of phenolic compounds as major constituents justifying its strong antioxidant potential performed in β-carotene test. The techniques used have shown effective strategies for the early detection of active natural products from plant extracts, as these approaches are still crucially absent. (Figure presented.).
Keywords: dereplication; HPLC-SPE-TT; Inga edulis; Medicinal plants; NMR; RP-HPLC-PDA